Pro ASP.NET 2.0 Website Programming - Armstrong, Damon (Apress, 2012)
Microsoft revolutionized web-application development with the original release of ASP.NET, increasing developer productivity to a level unmatched with any other technology. I have worked with Java, Perl, PHP, Cold Fusion, and ASP 3.0, and in my experiences, projects in ASP.NET took less time to build, were easier to maintain, simplified code reuse, and had a better return on investment. And that was just the first release. ASP.NET 2.0 includes a number of much needed additions that continue to set it apart as the leader in web-based development technologies. But functionality is meaningless unless applied correctly, and so the aim of this book is to discuss how to apply ASP.NET to solve real-world business issues.l